Online sexual abuse of adolescents by a perpetrator met online: a cross-sectional study - Linda S. Jonsson; Cecilia Fredlund; Gisela Priebe; Marie Wadsby; Carl Göran Svedin (BMC, 2019)
Abstract Background The current study aimed at exploring adolescents' experiences of online sexual contacts leading to online sexual abuse by a perpetrator whom the victim had first met online. Associations with socio demographic background, experience of abuse, relation to parents, health and risk behaviors were studied. Methods The participants were a representative national sample of 5175 students in the third year of the Swedish high school Swedish (M age = 17.97). Analyses included bivariate statistics and stepwise multiple logistic regression models. Results In total 330 (5.8%) adolescents had gotten to know someone during the preceding 12 months for the purpose of engaging in some kind of sexual activity online. Thirty-two (9.7%) of those, the index group, had felt that they had been persuaded, pressed or coerced on at least one occasion. Sexual interaction under pressure was seen as constituting sexual abuse. These adolescent victims of online sexual abuse, the index group, did not differ with respect to socio-demographic background from the adolescents without this experience, the reference group. The index group had significantly more prior experiences of different kind of abuse, indicating that they belong to a polyvictimized group. More frequent risk behavior, poorer psychological health, poorer relationships with parents and lower self-esteem also characterized the index group. Online sexual abuse, without experiences of offline abuse, was associated with a poorer psychological health, at least at the same level as offline sexual abuse only. Conclusions The study made clear the importance of viewing online sexual abuse as a serious form of sexual abuse. Professionals meeting these children need to focus not only on their psychological health such as symptoms of trauma and depression but also need to screen them for online behavior, online abuse and other forms of previous abuse.